Level of Corporate Social Responsibility Disclosure and Financial Performance: A Case Study in Ho Chi Minh City, Vietnam - Tran, Dinh Phung; Nguyen, Phan Thu Hang; Darsono, Susilo Nur Aji Cokro (Journal of Accounting and Investment, 2022)
Research aims: This study examines the influence of firm size, firm age, current ratio, and type of audit company on the corporate social responsibility disclosure level and its impact on the financial performance of listed enterprises in Vietnam. Design/Methodology/Approach: Financial data were collected from the annual reports of 109 enterprises listed on the Ho Chi Minh City Stock Exchange, Vietnam, from 2016 to 2020. This research employed the Random Effects Model (REM), Fixed Effects Model (FEM), and Feasible Generalized Least Squares (FGLS) to deal with the drawbacks of the regression models, as mentioned. Research findings: The findings support the positive influence of firm size, firm age, and the type of auditing firm on the level of CSR information disclosure of listed manufacturing enterprises. Also, the extent of CSR disclosure positively affected financial performance, confirming the positive relationship between CSR disclosure level and financial performance. Theoretical contribution/Originality: This study contributes to governance theory by expanding and combining stakeholder and legitimacy theories with criteria for measuring the level of CSR disclosure in the Vietnamese context. Therefore, the study results are a valuable reference for theorists who tirelessly pursue the CSR topic. Practitioner/Policy implication: This study proposes recommendations for practitioners who should focus on enhancing the level of CSR disclosure to generate more benefits and result in better financial performance. Also, policy implications should be raising the senior managers’ awareness of the level of CSR disclosure, firm size, firm age, and type of audit and establishing a stable legal framework for the level of CSR disclosure in line with international standards and practices. Research limitation/Implication: The sample data were only collected from manufacturing companies listed on Ho Chi Minh Stock Exchange, and the analyzed content and measurement of the level of CSR disclosure primely relied on the enterprises’ annual reports.